Sports Injuries Seen in Korfball Players: Assessment of Injuries’ Areas and Types - Mahmut Alp; Mahmut Özdinç (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to investigate sports injuries seen in korfball players according to injuries’ areas and types. A total of 118 (55 female, 63 male) Korfball players participated in the study voluntarily. The mean age of the athletes was 21.26±1.90 years, the mean height was 176.73±10.16 cm and the mean body weight was 69.75±12.87 kg. The Scandinavian Musculoskeletal Questionnaire (NMQ) was used to assess the disability of athletes. The body was divided into nine sections: neck, shoulder, elbow, wrist, back, waist, hip-thigh, knee, foot-ankle. Statistical package program was used to evaluate the data. The results were evaluated using frequency distribution and percentage distribution. When the highest frequency of injury was seen in 33.9% (n=40) of the foot-ankle, 19.5% (n=23) of the knee and 10.2% (n=12) of the back. The frequency of injury types by region is seen in the foot-ankle with 34.7% (n=41), knee with 19.5% (n=23), and in the back with 9.9% (n=12). According to the total frequency of injuries, it is seen that the biggest ratio is strain with 33% (n=39), sprain with 28% (n=33) and muscle pain with 14.3% (n=17). It has been found that a large proportion of injuries occur during training. The most common injuries were observed in the foot-ankle, knee and back regions. It is seen that 31.2% (n=37) of the athletes are treated in health institutions. Foot-ankle and knee injuries are the most common causes of injuries. As a result, it was determined that most of the korfball players were injured from foot-ankle, knee, back regions and the majority of these injuries occurred during trainings. It can be said that Sports Scientists can organize training programs according to the anatomical structures and physical characteristics of the athletes by taking care of good warm-up exercises